Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1096-8628(19990604)84:4<340::aid-ajmg6>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the prevalence of Down syndrome in Japan, 1980-1997

Abstract: The aims of the present study were to determine recent trends in the prevalence of Down syndrome (DS) in Japan, and to determine whether recent changes in demographic and social habits and access to prenatal diagnosis have influenced the livebirth rates of DS. Livebirth statistics indicate that the birth rate in Japan has decreased for women in their 20s and has increased for those in their 30s and 40s. During an 18-year period between 1980 and 1997, 1,299 consecutive DS infants were born among a total of 2,23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
4
25
2
Order By: Relevance
“…The effect of maternal age shown in this study is in agreement with several previous studies [7,20,21,23]. The removal of the effect of paternal age after adjustment for age of mother is very similar to recent analysis of Norwegian data [21] which showed relatively strong effect of paternal age almost completely explained by adjustment for maternal age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of maternal age shown in this study is in agreement with several previous studies [7,20,21,23]. The removal of the effect of paternal age after adjustment for age of mother is very similar to recent analysis of Norwegian data [21] which showed relatively strong effect of paternal age almost completely explained by adjustment for maternal age.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have been conducted to increase understanding of the Down syndrome epidemiology and its geographic variations [7-11]. The relation of advanced maternal age to an increased risk of Down syndrome has been established, but the effects of other risk factors have not been confirmed [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…15 This figure is lower than that seen in Western countries, 19 possibly because the prevalence of Down syndrome is lower in Japan. 20 Nevertheless, the present study underestimated the true mortality rates from CCVM in Japan.…”
Section: Study Limitationscontrasting
confidence: 62%
“…It was reported that DS prevalence was increased from 9.0 to 11.8 per 10,000 live births in 10 USA regions during a 25-year period (Olsen et al, 2003;Shin et al, 2009 The live birth prevalence of DS has been increasing in Japan since 1970; the increasing frequency of DS is attributed to advanced maternal age (Hoshi et al, 1999;Kajii, 2008;Takeuchi et al, 2008). In contrast, the live birth prevalence of DS has decreased (from 1.17 to 0.89/1000) over the years, from 1993 to 1998 in Singapore, due to antenatal diagnosis and elective abortion (Lai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%